Innovation Report - Design of a proof-of-concept Hybrid Solar Concentrator System Utilising Spectrum Beam Splitting Technology to generate sustainable heat and electricity, for palm oil processing farms in South-West Nigeria - Banjoko, Michael Olusegun (Cranfield University, 2025)
This research explores the potential of a hybrid solar energy system that combines Concentrated Solar Power (CSP) and Photovoltaics (PV) using spectrum beam-splitting technology to address energy shortages in Nigeria’s small-scale agro-industrial sector. By using cold and hot mirrors in a dish-based setup, the system separates the solar spectrum into visible and infrared bands for simultaneous electrical and thermal energy production, enabling cogeneration. Laboratory experiments, backed by theoretical modelling, show that this method can improve overall system efficiency, reduce PV overheating, and offer a reliable, modular, and sustainable energy solution. The innovation is situated within a design-based, neighbourhood-scale framework that aligns with regenerative sustainability principles. A real-life application is presented using the palm oil processing sector at Owodaiye Farms in Ijebu-Ife, Ogun State, Nigeria, as a demonstrator site. Here, the hybrid system not only meets off-grid energy demands but also catalyses local empowerment, circular economies, and thematic integration within agricultural tourism. The implications of this work extend beyond energy efficiency: the proposed system offers a replicable model for integrated rural development and community-based renewable energy infrastructure. It bridges the gap between technology and place-based regeneration by framing solar energy as a “Crude Sunlight Refinery”—a novel construct that envisions sunlight as a raw, separable, and usable resource for decentralized processing. Future research will investigate the scalability of this beam-splitting concept into modular solar refineries featuring fluid-based thermal receivers, enhanced optical coatings, and adaptive tracking mechanisms. Additionally, investigations into policy alignment, climate resilience metrics, and long-term techno-economic feasibility will strengthen its potential deployment across sub-Saharan Africa.
Sansom, Christopher L. - Associate Supervisor
Keywords: beam splitting; global thinking; hybridisation; Integrated farming; local acting; process heat